Stanniocalcin-1 Overexpression Prevents Depression-Like Behaviors Through Inhibition of the ROS/NF-κB Signaling Pathway - Chao, Bin; Zhang, Lili; Pan, Juhua; Zhang, Ying; Chen, Yuxia; Xu, Manman; Huang, Shijing (Frontiers in Psychiatry, 2021)
Background: Depression is a burdensome psychiatric disorder presenting with disordered inflammation and neural plasticity. We conducted this study with an aim to explore the effect of stanniocalcin-1 (STC1) on inflammation and neuron injury in rats with depression-like behaviors. Methods: A model of depression-like behaviors was established in Wistar rats by stress stimulation. Adeno-associated virus (AAV)-packaged STC1 overexpression sequence or siRNA against STC1 was introduced into rats to enhance or silence the STC1 expression. Moreover, we measured pro-inflammatory and anti-inflammatory proteins, superoxide dismutase (SOD), catalase (CAT), malondialdehyde (MDA) and reactive oxygen species (ROS) production. An in vitro model was induced in hippocampal neurons by CORT to explore the effect of STC1 on the neuron viability, toxicity and apoptosis. RT-qPCR and Western blot assay were employed to determine the expression of STC1 and nuclear factor κB (NF-κB) signaling pathway-related genes. Results: STC1 was under-expressed in the hippocampus of rats with depression-like behaviors, while its overexpression could reduce the depression-like behaviors in the stress-stimulated rats. Furthermore, overexpression of STC1 resulted in enhanced neural plasticity, reduced release of pro-inflammatory proteins, elevated SOD and CAT and diminished MDA level in the hippocampus of rats with depression-like behaviors. Overexpressed STC1 blocked the ROS/NF-κB signaling pathway, thereby enhancing the viability of CORT-treated neurons while repressing their toxicity and apoptosis. Conclusion: Collectively, overexpression of STC1 inhibits inflammation and protects neuron injury in rats with depression-like behaviors by inactivating the ROS/NF-κB signaling pathway.